Multilevel minimised delay clustering protocol for wireless sensor networks. (1st January 2014) - Abdel-Hady, Anar; Fahmy, Hossam M.A.; Abd El-Kader, Sherine M.; Eissa, Hussein S.; Salem, Ashraf
In this paper, a multilevel minimised delay clustering protocol (MMDCP) is proposed. MMDCP is proved to extend the lifetime of wireless sensor networks through levelling and through a better choice of cluster heads. MMDCP assigns the number of the lower level cluster heads and the leaf nodes in the network so as to minimise the end-to-end delay. When comparing MMDCP to LEACH-C, THCHP and Delay-Aware protocols; MMDCP succeeds in extending the lifetime of the network and in minimising the end-to-end delay and also in increasing throughput values. MMDCP also improves the structure of the network of delay-aware protocol. Two radio models are used in evaluation, the first order radio model and the discrete radio model. The obtained results are proved analytically and via simulation. These results make the proposed protocol a very good candidate for use in crises management applications like pre-expectation of landslides and early control of slum fires.